2021
DOI: 10.3390/su13052958
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Visitors to Romanian Ecotourism Destinations

Abstract: Visitors’ increasing interest in nature-based and cultural tourism, especially in the context of ecotourism destinations, has generated a heated debate in tourism literature. Some authors consider that ecotourism should be approached through a niche strategy rather than through mass marketing. Therefore, identifying the main characteristics of visitors to ecotourism destinations is very important in setting management and marketing strategies adapted to their specific needs. The present paper aims to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 36 publications
(38 reference statements)
2
17
0
Order By: Relevance
“…It should be noted that in accordance with Bonilla [25] (pp. 55-56), percentage attendance at cultural events in recent years has been sustained; however, there is attention to a stagnation in the participation of the population over the age of 18 in cultural events (see Figure 4).…”
Section: Boston Consulting Group Matrixsupporting
confidence: 52%
See 3 more Smart Citations
“…It should be noted that in accordance with Bonilla [25] (pp. 55-56), percentage attendance at cultural events in recent years has been sustained; however, there is attention to a stagnation in the participation of the population over the age of 18 in cultural events (see Figure 4).…”
Section: Boston Consulting Group Matrixsupporting
confidence: 52%
“…With regard to border tourism, it is important to note that the state receives more than 16 million international visitors and 11 million domestic visitors annually, taking advantage of a derived tourist potential with comparative advantages associated with its privileged geographical location with respect to the United States, which is characterized by being the third largest emitter of tourists [25] (p. 145).…”
Section: Boston Consulting Group Matrixmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be expected that those tourists with special interests in visiting a destination have different profiles to the average tourists found in the mass market destinations [79,80]. Studies have found that for some special interest tourism, such as golf tourism or ecotourism, tourists are younger and have greater expenditure at the destination, thereby requiring that they be satisfied with specific services directed to the practice of their interest or activity [79][80][81][82][83].…”
Section: Special Interest Tourism and Land Usementioning
confidence: 99%